2020
DOI: 10.1186/s40659-020-0271-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of protein profiles of the pellicle, gingival crevicular fluid, and saliva: possible origin of pellicle proteins

Abstract: Background: The pellicle, the acellular organic material deposited on the surface of tooth enamel, has been thought to be derived from saliva. In this study, protein compositions of the pellicle, gingival crevicular fluid, and saliva collected from healthy adults were compared to elucidate the origin of pellicle proteins. Results: The pellicle, gingival crevicular fluid, and saliva from the parotid gland or mixed gland were collected; subsequently, protein expression in samples from the respective individual w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 23 publications
(32 reference statements)
0
20
0
Order By: Relevance
“…However, this area was not included in our sampling because the AEP was collected from the middle and incisal/occlusal thirds of the tooth surface. Even though the influence of the crevicular fluid in the present experiment was probably minor, it is likely that some proteins of the pellicle originated from crevicular fluid, such as serotransferrin (23). One fundamental aspect of the present study is that the same volunteers took part in all three conditions.…”
Section: Discussionmentioning
confidence: 83%
“…However, this area was not included in our sampling because the AEP was collected from the middle and incisal/occlusal thirds of the tooth surface. Even though the influence of the crevicular fluid in the present experiment was probably minor, it is likely that some proteins of the pellicle originated from crevicular fluid, such as serotransferrin (23). One fundamental aspect of the present study is that the same volunteers took part in all three conditions.…”
Section: Discussionmentioning
confidence: 83%
“…One of its most important roles is helping to lubricate and protect the surfaces of the oral cavity. Saliva also appears to contribute to pellicle formation (Odanaka et al, 2020).…”
Section: Saliva In the Food Science Research Contextmentioning
confidence: 99%
“…In this study, we found Serotransferrin, fibrillin-1, components of immunoglobins, and collagen subtypes were among the most abundant proteins in terms of peptide hits. Serotransferrin is a glycoprotein known to be present in enamel pellicle and has a role in tooth morphogenesis [ 41 , 42 ] whereas, fibrillin-1 and collagens are extracellular matrix proteins. Collagen is the most abundant protein in dentin and also present in bone [ 5 ].…”
Section: Resultsmentioning
confidence: 99%